Geochemical characteristics of sediment and pore water affected by cold seeps in southern South China Sea - Chen, Chongmin; Wu, Xuewan; Wan, Zhifeng; Shang, Jiujing; Huang, Wei; Zhang, Wei; Liang, Jinqiang; Xiao, Zebang; Zhou, Wei; Zhong, Lifeng (Frontiers in Marine Science, 2023)
Cold seep, characterized by active material circulation and methane seepage, is of great importance to reconstruct the paleo-marine environment and trace the origin of life and the occurrence of minerals. Southern South China Sea (SCS) with ample oil and gas resources is an ideal platform for cold seep study, but information and researches on cold seeps here are rather deficient. We studied the geochemical characteristics of sediment cores and pore water combined with seismic profile information in the Beikang Basin, aiming to further understand the nature of cold seeps in this area. Results show the extremely low δ 13CDIC of pore water in each core and we also found sulfate content decreases with depth, the high content of inorganic carbon (DIC) and the corresponding minimumδ 13CDIC in pore water, the kink-type depth profiles of Sr, Ba and Ni enrichment factors and Sr/Mg in the sediments of BH-CL37, the reducing sedimentary environment constrained by the features of Mo, U and REE. The extremely negative δ 13CDIC in the pore water of the sediment cores indicates strong AOM effect in cold seeps and the main biogenic origin of methane. The SO42- depth variation trends of pore water, the high DIC content and the lowest value of δ 13CDIC can define the approximate SMTZ depth of each sediment core effectively. We thought that fluid fluxes and tectonic settings greatly influence the sedimentary environment and geochemistry, leading to the manifest regional differences in the properties and activities of cold seeps. This study of cold seep in southern SCS proves the variation of cold seep in time and space, stressing the necessity of further region-specific analysis towards different cold seeps; and the complex conditions of SCS do function well in offering multiple types of cold seeps.